Cognitive load assessment based on VR eye-tracking and biosensors - Vulpe-Grigorasi, Adrian (2023)
Funding Information: I would like to thank my supervisors Prof. Rui Neves Madeira and Dr. rer. nat. Vanessa Leung for their guidance and support in my PhD pursuit. I thank the E3UDRES2 alliance (Engaged and Entrepreneurial European University as Driver for European Smart and Sustainable Regions) for its cross-institutional research networking activities. I gratefully acknowledge support by the Austrian Research Promotion Agency FFG for the project EyeQTrack (COIN Aufbau FO999898083) and the Austrian Gesellschaft für Forschungs-förderung NÖ (Research Promotion Agency of Lower Austria) for the Competency Team Digital Health and Assistive Wellbeing (SP-FH20-003). Funding Information: I would like to thank my supervisors Prof. Rui Neves Madeira and Dr. rer. nat. Vanessa Leung for their guidance and support in my PhD pursuit. I thank the E3UDRES2 alliance (Engaged and Entrepreneurial European University as Driver for European Smart and Sustainable Regions) for its cross-institutional research networking activities. I gratefully acknowledge support by the Austrian Research Promotion Agency FFG for the project EyeQTrack (COIN Aufbau FO999898083) and the Austrian Gesellschaft fur Forschungsförderung NO (Research Promotion Agency of Lower Austria) for the Competency Team Digital Health and Assistive Wellbeing (SPFH20- 003). Publisher Copyright: © 2023 Owner/Author.